The real-work readiness of the grade 12 STEM students - Valdez, Angeline B.; Lapid-Ladwingon, Ruth R.; Baggas, Eunice W. (2019)
Despite the contrary embrace the K-12 education reform had received since its implementation in the Philippines in 2016, it has produced avenues for its graduates to be more equipped with necessary 21st century skills they used to embark on a journey in their chosen fields of specialization. One of its significant mandates in the implementation of work immersion for Senior High School Students. This study focused on identifying the 88 student's real-work readiness under the Science, Technology, Engineering, and Mathematics strand of Kalinga State University for the school year 2018-2019. It employed the descriptive qualitative research design to preset student's performance assessment in their work immersion. Data analysis included frequency count and computation of weighted mean. Results suggest that the students' attributes including work attitude, personally, and personal appearance, which they showed during their work immersion experience, were described as very good. However, there is a need to upgrade their work knowledge and discipline where they immersed in. The students' work knowledge could be enhanced through activities and tasks like field orientations and practical examinations initiated by their teachers in specialized subjects to prepare them to actual work during immersion. Also, it is suggested that they be given lectures on work ethics, communication in the workplace, stress management, and career orientation.
Keywords: Career development